Strategi Pemasaran Pada Pendidikan Dalam Menarik Minat Siswa Baru Di Kalukubula Preschool - Jumiati Jumiati; Elimawaty Rombe; Maskuri sutomo; Risnawati Risnawati4 (Lembaga Pengembangan Kinerja Dosen, 2024)
Education plays a crucial role in the life of every individual, especially during childhood. Therefore, educational institutions need to develop effective marketing strategies to attract new students. The focus of this research is to evaluate the educational marketing strategies implemented by Kalukubula Preschool Branch Kalukubula with the aim of increasing interest from new students.The method used in this research is qualitative with a case study approach. Data collection is conducted through in-depth interviews with various stakeholders, including the school principal, teachers, and parents. The research results indicate that Kalukubula Preschool Branch Kalukubula employs several educational marketing strategies, involving the development of quality educational programs, innovation in the learning system, improvement of facilities, and effective promotion. The findings of this research reveal that the educational marketing strategies implemented by Kalukubula Preschool Branch Kalukubula have successfully increased interest from new students through the development of quality educational programs, innovation in the learning system, improvement of facilities, and effective promotion